Lepus timidus Linnaeus 1758 - Robert S. Hoffmann (Smithsonian Institution Press, 1993)
Lepus timidus Linnaeus, 1758. Syst. Nat., 10th ed., 1:57. TYPE LOCALITY: "in Europa" [Uppsala, Sweden]. DISTRIBUTION: Palearctic from Scandinavia to E Siberia, except E Chukotsk (Russia), south to Sakhalin and Sikhote-Alin Mtns (Russia); Hokkaido (Japan); Heilungjiang, N Xinjiang (China); N Mongolia; Altai, N Tien Shan Mtns; N Ukraine, E Poland, and Baltics; isolated populations in the Alps, Scotland, Wales and Ireland. Introduced into England, Faeros and Scottish Isis. STATUS: Populations fluctuate, but none apparently threatened, except perhaps in Alps (Flux and Angermann, 1990). SYNONYMS: abet Kuroda, 1938; ainu Barrett-Hamilton, 1900; albus Leach, 1816; algidus Pallas, 1778; alpinus Erxleben, 1777; altaicus Barrett-Hamilton, 1900; begitschevi Koljuschev, 1936; borealis Pallas, 1778; breviauritus Hilzheimer, 1906; canescens Nilsson, 1844; collinus Nilsson, 1831; gichiganus J. Allen, 1903; hibernicus Bell, 1837; kamtschaticus Dybowski, 1922; kolymensis Ognev, 1923; kozhevnikovi Ognev, 1929; lugubris Kastschenko, 1899; lutescens Barrett-Hamilton, 1900; nwrdeni Goodwin, 1933; orii Kuroda, 1928; rubustus Urita, 1935; saghaliensis Abe, 1931; sclavonius Blyth, 1842; scoticus Hilzheimer, 1906; septentrionalis Link, 1795; sibiricorum Johanssen, 1923; sylvaticus Nilsson, 1831; transbaicalicus Ognev, 1929; typicus Barrett-Hamilton, 1900; variabilis Pallas, 1778; varronis Miller, 1901. COMMENTS: Subgenus Lepus (Gureev, 1964:180). Formerly included arcticus and othus; see Corbet (1978c:73); but also see comments under those species. A. J. Baker et al. (1983) found Scottish and Alpine populations morphologically distinct, as well as geographically isolated, from other populations, and Flux (1983) remarked that L. t. scoticus and L. t. hibernicus (from Scotland and Ireland, respectively), both introduced on the island of Mull (Hewson, 1991) still do not interbreed after 50 years. Published as part of Robert S. Hoffmann, 1993, Order Lagomorpha, pp. 807-827 in Mammal Species of the World (2 nd Edition), Washington and ...